Eskişehir'de siyasi hayat (1946-1960) - Sarı, Çağhan (My University, 2019)
Eskişehir’de Demokrat Parti teşkilatı 7 Mart 1946 yılında kurulmuştur. Kuruluşunda şehirdeki önemli toprak sahipleri ve iş adamları ön plana çıkmıştır. DP’nin 1946 yerel seçimlerini boykot etmesi nedeniyle Eskişehir’de de DP 26 Mayıs 1946 yerel seçimlerine katılmamıştır. 21 Temmuz 1946 genel seçimlerinde ise DP birinci parti çıkmış ve seçim yasasının neticesinde bütün milletvekillikleri DP listesinden çıkmıştır.

The Democratic Party organization in Eskişehir was established on March 7, 1946. Important landowners and businessmen in the city came to the fore. Since DP boycotted the local elections in 1946, he did not participate in the local elections of 26 May 1946 in Eskişehir. In the general elections of July 21, 1946, DP came out as the first party and as a result of the election law, all deputies were removed from the DP list
Keywords: Cumhuriyet Tarihi; Democratic party; Demokrat Parti; Eskişehir; Eskişehir (Turkey); Eskişehir (Türkiye); History; history of republic; local history; Politics and government; Politika ve idare; Tarih; Yerel Tarih Eskişehir